(untitled) (International Journal of Engineering and Computer Science, 2016)
The export of garment products to the world market has become very competitive in recent years. Buyers are demanding to get the products at lower price. Thus, the garment manufacturers need to minimize the cost of the product in order to sustain in the global market. Fabric covers the maximum cost of a garment in terms of percentage. If cost behind fabric can be minimized by utilizing maximum amount of fabric, the cost of the garment will definitely be lower. In this regard marker plays a very important role in usage of fabric. In this paper, we have studied an order where several markers were made in order to observe the influence of marker width to minimize the fabric cost. Finally, we found that marker width has a direct impact on fabric cost. With the change of width, the efficiency of the marker varies and ultimately the cost of fabric varies as well. So, the best width needs to be selected to minimize the fabric consumption and cost for an order.